Research on Responsible Innovation Mechanism Based on Prospect Theory - Qu, Xiaoyu; Wang, Xiao; Qin, Xutian (Sustainability, 2023)
In 2020, the new crown pneumoniaCOVID-19 epidemic swept the world, and it still has an impact on the production and lifestyle of various countries. Guiding enterprises to implement responsible innovation can enable enterprises to shoulder social responsibilities while innovating, resist the impact of the epidemic, accelerate countries to get out of the haze of the epidemic, and promote high-quality economic development. In this paper, three typical subjects of government, enterprise, and consumer are selected to construct an evolutionary game model, and prospect theory is introduced to explore the strategic choices and influencing factors of the three parties. Through the numerical simulation of MATLAB software, the following conclusions are obtained: in the early stage of policy implementation, the enthusiasm of enterprises to implement responsible innovation is not high; with the implementation of policies and the continuation of time, the enthusiasm of enterprises gradually increases; and the supervision role of the government and consumers gradually decreases. Appropriate government incentives and disincentives will promote enterprises and consumers to participate in responsible innovation. This paper explores the game process of government, enterprises, and consumers from a dynamic perspective, explores the decision-making process of all parties under the prospect theory, reveals the implementation process of responsible innovation and the factors affecting responsible innovation, and provides a theoretical reference for the implementation of responsible innovation model.